USING ORAL QUESTIONING TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ACTIVENESS - Suhardi, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed at improving students’ speaking activeness using Oral Questioning Technique in teaching learning process. The subject of this research was the 10th grade students of Multimedia class at SMK Mandiri Pontianak academic year 2016/2017. This research was done by asking nd answering the materials to make the students active in speaking. The method of this research was a classroom action research. The researcher observed the improvement of students’ activeness in speaking by collecting data through observation and measurement technique. The data were in the form of observation checklist, field notes, and activeness table. The data were collected by analyzing field notes and observation guidelines during the research and by measuring the students ‘individual score in activeness. The result of this research showed that Oral Questioning Technique can improve the students’ activeness in speaking. The students’ individual score in activeness also improved in teaching learning process. From the result, it can be concluded that students’ activeness in speaking taught by Oral Questioning Technique was improved. In addition, this technique can help students to speak actively. Keywords: Oral Questioning Technique, Multimedia Students, Activeness in Speaking, Classroom Action Research.